2019
DOI: 10.3892/mco.2019.1869
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characteristics of breast cancer according to clinicopathological factors

Abstract: The purpose of the present study was to evaluate the correlation between molecular factors such as BRCA1 DNA repair associated (BRCA1), checkpoint kinase 2 (CHEK2) and nucleotide binding oligomerization domain containing 2 (NOD2) gene mutations and clinicopathological factors in patients with breast cancer (BC). Prognostic factors were analyzed in BC patients with confirmed BRCA1 (n=73), CHEK2 (n=51) and NOD2 (n=31) mutations. The control group was selected from BC patients without mutations (n=392). The BRCA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 31 publications
0
13
0
3
Order By: Relevance
“…NOD2 increases the risk of breast cancer [ 22 ], the research showed that the overexpression of NOD2 inhibited cell proliferation and promoted clone formation in three negative breast cancer cell lines [ 23 ]. The incidence of lymph nodes without metastatic is higher in carriers of NOD2 mutations as a prognostic factor [ 24 ]. Therefore, the positive correlation between NOD2 and PITX1 gene is reliable.…”
Section: Discussionmentioning
confidence: 99%
“…NOD2 increases the risk of breast cancer [ 22 ], the research showed that the overexpression of NOD2 inhibited cell proliferation and promoted clone formation in three negative breast cancer cell lines [ 23 ]. The incidence of lymph nodes without metastatic is higher in carriers of NOD2 mutations as a prognostic factor [ 24 ]. Therefore, the positive correlation between NOD2 and PITX1 gene is reliable.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin D with the cooperation of CDK4/6 regulates the events is the early G1 phase. Cyclin E-CDK2 are responsible to initiate S phase, Cyclin A with CDK2 and then CDK1 involve in the completion of S phase for entry into mitosis, and Cyclin B-CDK1 fascinate this entry expression of cytokeratin (CK) 5/6 and CK14 with sporadic basal carcinoma [25].…”
Section: Brca1mentioning
confidence: 99%
“…BRCA1 mutated breast cancer is known to be triple-negative breast cancers (TNBC), characterized by negative estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2). However, they manifest the same immunohistochemical profiles for the positive expression of cytokeratin (CK) 5/6 and CK14 with sporadic basal carcinoma [ 25 ].…”
Section: Brca1mentioning
confidence: 99%
“…рисунок). Количество опухолей с отрицательным статусом РЭ при носительстве BRCA1-мутации значительно выше, чем в общей группе больных РМЖ, и варьирует в диапазоне 67-88 % [2][3][4][8][9][10][11][12]. Полученный нами показатель 72,7 % соответствует данным других работ.…”
Section: Introductionunclassified
“…J. Huszno и соавт. отнесли к подтипу LumВ-27 % опухолей, к LumA -7 % [12]. В работе I. Sønderstrup и соавт.…”
Section: Introductionunclassified